Keith Haring in Pisa and Melbourne: Controversy and conservation. (1st June 2016) - Dickens, Jenny; Rava, Antonio; Colombini, Maria Perla; Picollo, Marcello; Shank, Will
Abstract : Keith Haring painted large outdoor murals in Melbourne, Australia, in 1984 (the Collingwood Mural ) and at Pisa in Italy in 1989 ( Tuttomondo ). Recently, both murals have been analyzed and conserved by similar teams of conservators and scientists. The original appearance of the Collingwood Mural was severely compromised, and the original materials much degraded. Tuttomondo was somewhat altered visually but with less physical damage. There were initial suggestions to repaint Tuttomondo but these were dissipated by good communication of the analytical findings. In Melbourne, there was a high-profile and emotive campaign to have the Collingwood Mural repainted. Conservators and government were heavily criticized for supposedly ignoring the artist's wishes. However, detailed research into Haring's published statements revealed that conservation does respect his artistic aims. For the Collingwood Mural, conservators had to consider whether to reduce the visual disturbances which obscured the works. Practices documented by conservation theorists and routinely undertaken by conservators guided the decision to apply mechanically reversible re-integration. This made Haring's unique 'line' visible and accessible again, and pleased the public. The controversies showed how conservators must communicate clearly and tactfully; appreciate the feelings of the public and involve communities in conservation, without compromising rigorous scientific and curatorial research.